American Orthopaedic Association's (AOA) Council of Orthopaedic Residency Directors (CORD) 2021 Summer CORD Conference: Top 10 Abstracts. Issue 3 (15th July 2022) - LaPorte, Dawn M.; Patt, Joshua C.
Abstract : In a continuing collaboration between the American Orthopaedic Association's (AOA) Council of Orthopaedic Residency Directors (CORD) and the JBJS, the following 10 abstracts highlight the scientific research presented at AOA's virtual annual national meeting held in June 2021. These abstracts embody CORD's purpose and mission:"The American Orthopaedic Association's Council of Orthopaedic Residency Directors (CORD) program strives to recognize best practices in orthopaedic residency education and fellowship education based on Accreditation Council for Graduate Medical Education (ACGME)-defined essential knowledge and skills in each of the residency education competency areas. CORD provides a forum for academic orthopaedic leaders to exchange ideas, discuss solutions to challenges, and find ways to teach residents in orthopaedic programs effectively." We hope this education-related research will inspire further inquiry to advance the development of future orthopaedic surgeons.